The Buying Pattern of Energy Drink and its Use among the Young Generation of Saudi Arabia - Zulfeequar Alam, Mohammad (British Journal of Marketing Studies, 2017)
Energy drink intake has to turn into a favorite exercise around the world, in particular among the younger generation. In Saudi Arabia, there are significant limitations in energy drinks – in abstract, tastes, advertising, the attention of sponsorship, are not permitted," however, it is not limited to the use of social media. The core purpose of this study is to investigate the consumption patterns of energy drinks among young people in Saudi Arabia even after partial restrictions on the promotion of energy drinks. This method of the research was used an exploratory approach in nature with the data collection through survey method (Maxim, 1999) were gathered from the respondents. A self-administered structured questionnaire was developed using survey monkey online services. After getting the responses, the data were edited, tabulated and analyzed using descriptive statistics (Frequency distribution) through the excel sheet and the result was explained accordingly. The result reveals that there is a trend of widespread use of energy drinks among young people, especially students in the age group 23-27 (72.10%). It also indicates that there is a high level of social acceptance of energy drink consumption in the region. The respondents showed a tendency towards buying decisions of it, but between the choice of brands, a certain degree of loyalty was shown. There is a call of some awareness program to increase the knowledge among the youth about the consumption of energy drinks and their effects on health.